2012
DOI: 10.1590/s0101-31222012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil fertility and its relationship with seed physiological potential in a soybean production area

Abstract: -The correlation of soil fertility x seed physiological potential is very important in the area of seed technology but results published with that theme are contradictory. For this reason, this study to evaluate the correlations between soil chemical properties and physiological potential of soybean seeds. On georeferenced points, both soil and seeds were sampled for analysis of soil fertility and seed physiological potential. Data were assessed by the following analyses: descriptive statistics; Pearson's line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 11 publications
4
17
1
7
Order By: Relevance
“…As for seeds, it is necessary that accumulation of reserves occurs adequately because the initial development of seedlings depends on these substances (Veiga et al, 2010). Mondo et al (2012) found that the correlation between fertility and physiological potential of the seed is relevant for soybean seed technology.…”
Section: Introductionmentioning
confidence: 99%
“…As for seeds, it is necessary that accumulation of reserves occurs adequately because the initial development of seedlings depends on these substances (Veiga et al, 2010). Mondo et al (2012) found that the correlation between fertility and physiological potential of the seed is relevant for soybean seed technology.…”
Section: Introductionmentioning
confidence: 99%
“…Mann et al (2002) found increases in germination in both modes of application of Mn, on soil and on leaf, with higher efficiency of foliar application, but the same was not observed by Melarato et al (2002). Conversely, Mondo et al (2012) registered a negative correlation between Mn content in the soil and germination of soybean seeds.…”
Section: Germinationmentioning
confidence: 77%
“…In most cases, these recommendations emphasize the effect of mineral nutrition on yield, not correlating with seed quality. Mondo et al (2012) performed soil and seed samplings at georeferenced sites for analysis of soil fertility and physiological potential of soybean seeds, and concluded that the correlation between these factors is very important for seed production technology.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos têm sido realizados com o objetivo de estabelecer correlações entre a produtividade das culturas e propriedades físico-químicas do solo, bem como outras variáveis, estabelecendo os principais fatores de influência (MONDO et al, 2012). Na agricultura de precisão, o solo deixa de ser tratado como homogêneo e a sua variação espacial passa a ser considerada visando a exploração e monitoramento das características produtivas, tornando-se uma estraté-gia de manejo que busca a racionalização do uso de insumos, tais como agrotóxicos e fertilizantes, associado à preservação dos recursos naturais (MESTAS et al, 2010;SOUZA et al, 2010;RESENDE et al, 2014).…”
Section: Introductionunclassified
“…A disponibilidade de áreas com estas características, no entanto, não sempre ocorre, resultando na necessidade da utilização de solos com média a baixa fertilidade (PESKE et al, 2012). Neste contexto, mapas de distribuição espacial das características do solo mostram a acentuada variabilidade de ambiente que as plantas podem encontrar em uma lavoura (MONDO et al, 2012).…”
Section: Introductionunclassified